Facile Modification of LiAlCl4 Electrolytes for Mg-Li Hybrid Batteries by the Conditioning-Free Method - Cho, Jae-Hyun; Ha, Jung Hoon; Oh, Jinwoo; Lee, Sue Bin; Kim, Kwang-Bum; Lee, Kwan-Young; Lee, Jae Kyun (American Chemical Society, 2020)
Lithium aluminum chloride complexes (LACCs) are excellent electrolyte candidates for Mg-Li hybrid batteries (MgHBs) because they can simultaneously conduct electrochemical reactions both at Mg anodes and Li+- insertion cathodes. However, to ensure compatibility with Mg anodes, LACCs must first undergo a cumbersome conditioning process; this severely lowers their productivity and limits any improvement in the electrolyte performance. To resolve this issue, we employed a conditioning-free process for the facile modification of LACCs. The conditioning-free process was conducted by reacting LACCs and metallic Mg powder with a small amount of CrCl3 that promotes the rapid and high-degree substitution of oxidation states between anionic Al3+ complexes and Mg. The newly generated Mg2+ ions in the conditioning-free LACC (cf-LACC) reached a high concentration of up to 1.2 M and formed anionic complexes that function as charge carriers for Mg anodes. Moreover, the cf-LACC electrolyte successfully demonstrated its applicability to the MgHB system, which used a high voltage cathode material LiFePO4, by exhibiting excellent rate capability and cyclability.